2014
DOI: 10.1088/0004-637x/781/1/40
|View full text |Cite
|
Sign up to set email alerts
|

METAL-POOR STARS OBSERVED WITH THE MAGELLAN TELESCOPE. II. DISCOVERY OF FOUR STARS WITH [Fe/H] ⩽ –3.5

Abstract: We report on the discovery of seven low-metallicity stars selected from the Hamburg/ESO Survey, six of which are extremely metal-poor (EMP, [Fe/H] −3.0), with four having [Fe/H] −3.5. Chemical abundances or upper limits are derived for these stars based on high-resolution (R ∼ 35,000) Magellan/MIKE spectroscopy, and are in general agreement with those of other very and extremely metal-poor stars reported in the literature. Accurate metallicities and abundance patterns for stars in this metallicity range are of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 107 publications
(163 reference statements)
2
46
1
Order By: Relevance
“…to the heavier neutron-capture element Ba, as have been found in several studies (e.g., Honda et al 2004;Aoki et al 2005Aoki et al , 2013aLai et al 2008;Hollek et al 2011;Cohen et al 2013;Placco et al 2014a). Such stars are generally taken as evidence for an extra neutron-capture element production mechanism in addition to the main r-process as the source of the heaviest elements in the early universe (e.g., Travaglio et al 2004;Honda et al 2006;Sneden et al 2008;Jacobson & Frebel 2014).…”
Section: A Newmentioning
confidence: 78%
See 2 more Smart Citations
“…to the heavier neutron-capture element Ba, as have been found in several studies (e.g., Honda et al 2004;Aoki et al 2005Aoki et al , 2013aLai et al 2008;Hollek et al 2011;Cohen et al 2013;Placco et al 2014a). Such stars are generally taken as evidence for an extra neutron-capture element production mechanism in addition to the main r-process as the source of the heaviest elements in the early universe (e.g., Travaglio et al 2004;Honda et al 2006;Sneden et al 2008;Jacobson & Frebel 2014).…”
Section: A Newmentioning
confidence: 78%
“…Based on a large literature sample, Aoki et al (2013b) Placco et al (2014a) suggested this was due to the small/incomplete sample of stars in this metallicity regime; the bottom panel of Figure 13 lends support to this argument (see also Li et al 2015). Roughly half of the stars below…”
Section: Neutron-capture Elementsmentioning
confidence: 81%
See 1 more Smart Citation
“…Since HE0020-1741 is on the upper red giant branch, the observed carbon abundance does not reflect the chemical composition of its natal gas cloud. By using the procedure described in Placco et al (2014b), which interpolates the observed g log , [ ] Fe H , and [ ] C Fe of HE0020-1741 with a grid of theoretical stellar evolution models for low-mass stars, we determine the carbon depletion due to CN processing for HE0020-1741 to be 0.34 dex.…”
Section: Chemical Abundances and Upper Limitsmentioning
confidence: 99%
“…Because of that, we included the observed carbon and nitrogen abundances for all the syntheses, as well as the 12 C/ 13 C isotope ratio. (Placco et al 2014b).…”
Section: Neutron-capture Elementsmentioning
confidence: 99%